Toilet Training in Preschool - Wijayaningsih, Ambarwati; Yuwono, Susatyo (Universitas Muhammadiyah Surakarta, 2019)
Purpose: This study aims to understand the dynamics of the implementation of toilet training in preschool child. Methodology: This research uses descriptive qualitative approaches by selecting informants using purposive techniques. The informants in this study consisted of working mothers and housewives who have their first child at preschool age and successful and unsuccessful toilet training, and live with a nuclear family. The number of research informants are 8 people. Data collection techniques using semi-structured interviews. Results: The results shows that the methods or methods taught by mothers included when starting toilet training, modeling techniques, oral techniques, using tools for elimination, managing time, adjusting the child’s condition, and not waking the child at the mall day. The influencing factors come from the child, the mother, and the environment. Some of which are experiences, social environment support, knowledge, motivation, emotional feelings of the mother, parenting, and the child’s attitude and behavior to be conditioned. Then the effect resulting from the implementation of toilet training are the child’s attitude, social development, emotional, and knowledge of children, communicative children, parenting, economic, emotional feelings of the mother, and the level of independence of the child. The results obtained are quite diverse and there is a uniqueness in each informant.